2018
DOI: 10.18632/oncotarget.24751
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antibiotic treatment on immune-checkpoint blockade efficacy in advanced non-squamous non-small cell lung cancer

Abstract: IntroductionDespite durable responses from immune-checkpoint blockade (ICB) in a subset of patients with advanced non-small cell lung cancer (NSCLC), the majority of patients do not derive benefit from this treatment. In this analysis we evaluated the impact of concomitant administration of antibiotics during initiation of ICB on clinical outcome.MethodsAdvanced non-squamous NSCLC patients receiving ICB as second- or later line between 2015 and 2017 at our tertiary cancer center in Salzburg (Austria) were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
49
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 14 publications
12
49
2
2
Order By: Relevance
“…Contrary to established data demonstrating that antibiotic treatment leads to a uniform downregulation of both allo-and tumor-specific immunity, [6][7][8][9] we now demonstrate that in certain individuals dysbiosis can drastically alter pulmonary and systemic levels of CD4 + Foxp3 + regulatory T cells, thus increasing both acute and chronic rejection.…”
Section: Introductioncontrasting
confidence: 96%
“…Contrary to established data demonstrating that antibiotic treatment leads to a uniform downregulation of both allo-and tumor-specific immunity, [6][7][8][9] we now demonstrate that in certain individuals dysbiosis can drastically alter pulmonary and systemic levels of CD4 + Foxp3 + regulatory T cells, thus increasing both acute and chronic rejection.…”
Section: Introductioncontrasting
confidence: 96%
“…Four other studies in the lung cancer population showed a similar trend. Despite various rates of prescription of ATB in these studies, all of them showed shorter OS and PFS in the ATB groups [51][52][53].…”
Section: Atb-related Dysbiosis and Impact Of Atb On Efficacy Of Immunmentioning
confidence: 82%
“…Indeed, Dubin et al [8] found increased representation of bacteria belonging to the Bacteroidetes phylum to be correlated with a lower incidence of checkpoint-blockade-induced colitis in 34 patients with metastatic melanoma undergoing ipilimumab treatment. In addition, concomitant use of antibiotics (affecting the composition of the gut microbiota) during initiation of immune checkpoint inhibitors has been evaluated in 30 NSCLC patients with respect to clinical outcomes and irAE [9]. Although not statistically significant, irAE occurred in 27.3 and 57.9% in patients with and without antibiotic use, respectively [9].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In addition, concomitant use of antibiotics (affecting the composition of the gut microbiota) during initiation of immune checkpoint inhibitors has been evaluated in 30 NSCLC patients with respect to clinical outcomes and irAE [9]. Although not statistically significant, irAE occurred in 27.3 and 57.9% in patients with and without antibiotic use, respectively [9]. Conversely, antibiotics use has also been associated with reduced efficacy [9, 10].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation